Wickedness : a philosophical essay - Midgley, Mary (Routledge, 2001)
To look into the darkness of the human soul is a frightening venture. Here Mary Midgley does so, with her customary brilliance and clarity. In Wickedness she sets out to delineate not so much the nature of wickedness as its actual sources. Midgley's analysis proves that the capacity for real wickedness is an inevitable part of human nature. This is not however a blanket acceptance of evil. She provides us with a framework that accepts its existence yet offers humankind the possibility of rejecting this part of our nature. Out of this dark journey she returns with an offering to us: an understanding of human nature that enhances our very humanity. To read Wickedness is to understand Mary Midgley's reputation as one of the world's greatest moral philosophers.